2016
DOI: 10.1039/c6ra06953c
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescence probe based on p-acid-Br and its application in thiourea detection

Abstract: A novel organic fluorescence system was developed to detect thiourea based on p-acid-Br, which in the range of 0.5–1000 nM and with a detection limit of 0.26 nM. And this method provides a new promising platform for clinical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thiourea, which is the main raw material for medicine, pesticides, fertilizer, silk industry, agriculture, metal processing and so on [10a–c], has been reported that Pb 2+ could be highly absorbed by thiourea [11a–c]. Therefore, it could be considered that thiourea and pyrrole are simultaneously polymerized to form poly(pyrrole thiourea), and S atom of thiourea is introduced into the polymer to increase the active site of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Thiourea, which is the main raw material for medicine, pesticides, fertilizer, silk industry, agriculture, metal processing and so on [10a–c], has been reported that Pb 2+ could be highly absorbed by thiourea [11a–c]. Therefore, it could be considered that thiourea and pyrrole are simultaneously polymerized to form poly(pyrrole thiourea), and S atom of thiourea is introduced into the polymer to increase the active site of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence sensors employ a fluorescent signal for the detection of analytes. In order to detect different organics at an earlier stage of a disease development, a low detection limit of the organics is desirable [33]. Thiourea derivatives possess the ability to detect both anions and cations and are therefore attracting the attention to be versatile detectors in coming decades [5].…”
Section: Introductionmentioning
confidence: 99%